A Systematic Study of the Mass Transport, Kinetic and Thermodynamic Properties of the FeIII/II Process at Glassy Carbon and Boron-Doped Diamond Electrodes. (20th September 2017) - Lin, Mingyue; Li, Jiezhen; Pan, Dawei; Bond, Alan M.; Zhang, Jie
Graphical abstract: Highlights: The Fe III/II processes were investigated using Fourier transformed ac voltammetry. The k 0 values at a BDD electrode are smaller than a glassy carbon electrode. k 0 is electrolyte anion dependent. The measured k 0 values at a BDD electrode display harmonic dependence. Electrode heterogeneity effect on the measured k 0 values was revealed. Abstract: The heterogeneous electron transfer kinetics ( k 0 values), mass transport and thermodynamic properties ( E 0 values) associated with the Fe III/II process have been determined in aqueous solutions containing 0.1 M HCl, HClO4, bis(trifluoromethanesulfonyl)imide (HNTf2 ) or 0.05 M silicotungstic acid (H4 [ α- SiW12 O40 ]) supporting electrolytes. The diffusion coefficient ( D ) values for Fe III and Fe II are dependent on the radius of the electrolyte anion and follow the order D (SiW12 O40 4− ) < D (NTf2 − ) < D (ClO4 − ) < D (Cl − ). The k 0 values are found to be smaller at boron doped diamond (BDD) electrodes than glassy carbon (GC) electrodes, and influenced by the ion-pairing between electrolyte anions and Fe III and Fe II . Based on the formal potential value, HNTf2 is found to be a more innocent electrolyte than commonly used HClO4 with regard to determine the true k 0 values of the outer-sphere [Fe(H2 O)6 ] 3+/2+ process. Fourier transformed large amplitude alternating current voltammetry, which provides favorable signal to background ratio, was used to determine k 0 values associated with the Fe III/II process in H4 [ α- SiW12 O40 ] and HNTf2 electrolyte media at GC electrodes and probe the implications of the heterogeneity of the BDD electrode surface on the electrode kinetic determination in H4 [ α- SiW12 O40 ] electrolyte media.